Perceptions of the activity, the social climate, and the self during group exercise classes regulate intrinsic satisfaction - Maher, Jaclyn P.; Gottschall, Jinger S.; Conroy, David E. (Frontiers in Psychology, 2015)
Engaging in regular physical activity is a challenging task for many adults. Intrinsic satisfaction with exercise classes is thought to promote adherence to physical activity. This study examined the characteristics of exercise classes that impact within-person changes in intrinsic satisfaction over the course of an extended group exercise program. A 30-week physical activity trial was conducted with assessments at the end of each class. Community-living adults (n=29) were instructed to complete at least 6 group exercise classes each week and, following each exercise class, complete a questionnaire asking about the characteristics of the class and the participant’s evaluation of the class. Intrinsic satisfaction was high, on average, but varied as much within-person from class-to-class as it did between exercisers. Participants reported the greatest intrinsic satisfaction when classes placed greater emphasis on exercisers’ involvement with the group task, feelings of competence, and encouragement from the instructor. For the most part, exercise classes that were more intense than usual were perceived by exercisers as less intrinsically satisfying. Some overall characteristics of the exercise classes were also associated with intrinsic satisfaction. The social and motivational characteristics of group exercise classes contribute to exercisers’ intrinsic satisfaction with classes and attention to those dynamics, as well as the intensity of the exercise, may improve adherence for exercise regimens.